2009
DOI: 10.1016/j.bbamcr.2008.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characterization of a novel, permanently active S100P mutant

Abstract: S100 proteins function as Ca2+ signal transducers by regulating cellular targets in their Ca2+ bound conformation. S100P is a member of the S100 protein family that can activate the membrane and F-actin binding protein ezrin in a Ca2+ dependent manner at least in vitro. Here we generated a novel tool to elucidate directly the S100P-ezrin interaction in vivo. This was achieved by constructing a S100P derivative that contained mutations in the two EF hand loops predicted to lock the protein in a permanently acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Although extracellular S100P stimulates cell proliferation by RAGE, 5 Austermann et al 7,8 have shown S100Pmediated activation of ezrin and suggested that the interaction between S100P and ezrin promotes a migration of tumor cells and metastatic potential. Our study has shown that S100P expression is significantly correlated with ezrin expression, not with RAGE expression, in ICC tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Although extracellular S100P stimulates cell proliferation by RAGE, 5 Austermann et al 7,8 have shown S100Pmediated activation of ezrin and suggested that the interaction between S100P and ezrin promotes a migration of tumor cells and metastatic potential. Our study has shown that S100P expression is significantly correlated with ezrin expression, not with RAGE expression, in ICC tissue.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this problem, 'permanently active' S100P (S100P-PA) was used and the use of ionophores or thapsigargin was avoided. Following the report of Austermann et al [28], we constructed S100P-PA that contained mutations in the two EF-hand loops predicted to lock the protein in a permanently active state. When S100P-PA was transfected into Huh-7 with Bcl-2, a significant decrease in the protein level of Bcl-2 was observed along with elevation of the cellular levels of S100P-PA ( Figure 6D).…”
Section: Figure 4 Effects Of S100 Proteins On the Fkbp38-bcl-2 Interamentioning
confidence: 99%
“…The Bcl-2 transmembrane deletion mutant (residues 219-239; Bcl-2 C21) was subcloned into pMAL-c2x. pME18S-permanently active S100P (S100P-PA) was prepared as described previously [28].…”
Section: Antibodiesmentioning
confidence: 99%
“…The construction of the pET11a-S100 and pME18S-S100 plasmids was reported previously (18). A permanently active S100P (S100P-PA) was prepared as described (19). To create a pcDNA3-Tau plasmid, the human Tau441 cDNA was purchased from Addgene and cloned into the pcDNA3 vector.…”
Section: Methodsmentioning
confidence: 99%
“…To overcome this problem, "permanently active S100P" (S100P-PA) was used, and the use of ionophore or thapsigargin was avoided. Followed the report of Austermann et al (19), we constructed S100P-PA that contained mutations in the two EF-hand loops predicted to lock the protein in a permanently active state. Similar to S100A1, S100A2, S100A6, and S100B (Fig.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%